2016
DOI: 10.1002/smr.1789
|View full text |Cite
|
Sign up to set email alerts
|

A bug reproduction approach based on directed model checking and crash traces

Abstract: Reproducing a bug that caused a system to crash is an important task for uncovering the causes of the crash and providing appropriate fixes. In this paper, we propose a novel crash reproduction approach that combines directed model checking and backward slicing to identify the program statements needed to reproduce a crash. Our approach, named JCHARMING (Java CrasH Automatic Reproduction by directed Model checkING), uses information found in crash traces combined with static program slices to guide a model che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…While BugRedux [14] is based on forward symbolic execution, Star [4] is a more recent approach that applies optimized backward symbolic execution on the method calls recorded in a stack trace in order to compute the input parameters that trigger the target crash. JCharming [19] is also based on using crash stack traces as the only source of information about a reported crash.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…While BugRedux [14] is based on forward symbolic execution, Star [4] is a more recent approach that applies optimized backward symbolic execution on the method calls recorded in a stack trace in order to compute the input parameters that trigger the target crash. JCharming [19] is also based on using crash stack traces as the only source of information about a reported crash.…”
Section: Related Workmentioning
confidence: 99%
“…JCharming [19] applies directed model checking to identify the pre-conditions and input parameters that cause the target crash. Finally, ConCrash [3] is a recent approach that focuses on reproducing concurrency crashes, in particular.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…To help developers in this process, various automated techniques have been suggested. These techniques typically either use program runtime data (Artzi et al 2008;Clause and Orso 2007;Narayanasamy et al 2005;Steven et al 2000;Gómez et al 2016;Bell et al 2013;Cao et al 2014;Rößler et al 2013) or crash stack traces (Bianchi et al 2017;Soltani et al 2017;Nayrolles et al 2017;Xuan et al 2015;Chen and Kim 2015) to generate a test case that triggers the reported crash.…”
mentioning
confidence: 99%